Integrasi Etnopedagogi dalam Mengembangkan Model Pembelajaran Biologi - Iwan Setia Kurniawan; Rifki Survani (Jurnal Konseling dan Pendidikan, 2018)
Model of learning is a syntax or learning steps depicted from the beginning to the end presented in full or typical in the learning process. This study aims to determine the ability of biology pre-service teacher in developing biology learning model integrated ethno pedagogy. This research is a quantitative descriptive research, data obtained based on the results of data analysis is described to obtain information or description of the results of this study. Population in this study as many as 164 students are divided into 38 groups. Technique of data collecting with non-test, data obtained from document of assignment of student report given score based on its indicator which divided into some aspect of assessment and student response questionnaire. The results showed that the ability of biology pre-service teacher in developing the learning model oriented ethno pedagogy including sufficient category with an average score of 75. Students’ response to development of learning model oriented ethno pedagogy is good, 70.04% of students expected. Thus it can be concluded that the ability of students in developing biology learning model integrated ethno pedagogy still needs to be developed especially for several aspects. The results of this study can be used as a reference for the lecture program in the future.